Whither Quo vadis?: [Sienkiewicz's novel in film and television] - Scodel, Ruth (Wiley-Blackwell, 2009)
Novel and film -- Adapting the narrative -- Gender and ethnicity -- Political institutions, political subtexts -- The complex allusions of the 1985 miniseries -- The Roman people -- Religion and religious authority in Quo vadis? -- Conclusions -- Exkursus : Chilo's mother : a peculiarity of the German translations of Quo vadis?